DETERMINANTS OF OUTPATIENT CARE BEHAVIOR OF THE ELDERLY POPULATION IN WEST SULAWESI IN 2022: BACKWARD ELIMINATION LOGISTIC REGRESSION - Tengku Natasya Auzea Fahyumi; Nofita Istiana (Jurnal Statistika Universitas Muhammadiyah Semarang, 2025)
Ageing population is a result of the successful development. It is characterized by an increase in the number and proportion of the elderly population. The elderly population is described as a vulnerable group. As a result of degenerative process in physical, psychological, and social activity aspects, the elderly population has a high risk of experiencing health problems. West Sulawesi is the province with the eighth highest morbidity rate for the elderly. However, this province has the lowest percentage of outpatient care, at 36,39%. Therefore, it is necessary to conduct research on the outpatient care behavior of the elderly in West Sulawesi in 2022. This research uses a binary logistic regression method. The results show that the variables marital status, education level, disability status, and activity impairment have a significant effect on outpatient care behavior in West Sulawesi in 2022. Efforts from the government and the society are needed to increase the awareness about the importance of health checks among the elderly.